PENGARUH EKUITAS MEREK DAN COUNTRY OF ORIGIN TERHADAP KEPUTUSAN PEMBELIAN MOBIL TOYOTA DI PASAMAN BARAT - Eko Putra (Jurnal Apresiasi Ekonomi, 2015)
This research is to find out how Brand equity and country of origin affect the purchase decision of Toyota in Pasaman barat. The result shows that brand equity’s variable (X1) and country of origin (X2) significantly affect the Purchase Decision (Y) with significant rate 0,000. The amount of, the influence of Brand Equity (X1) and Country of origin (X2) on Purchase`Decision (Y) is 0,334 or 33,4% that means the contribution of brand equity and country of origin’s influence on purchase decision of Toyota in Pasaman Barat is 33,4%. 66,6% influenced by other variables which are not included in this research. Keywords : Brand Equity, Country Of Origin dan Purchase Order